THE IMPACT OF TECHNOLOGY ON STUDENT LEARNING OUTCOMES - Kabirova Fotimaizahro, (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
The integration of technology into education has significantly transformed teaching and learning processes in recent years. Digital tools, online platforms, and interactive resources have created new opportunities for students to access information and develop academic skills. This article examines how technology influences student learning outcomes, focusing on engagement, academic performance, and independent learning abilities. The study also discusses both the advantages and challenges associated with educational technologies. The findings suggest that when used effectively, technology can enhance learning efficiency, promote collaboration, and support personalized education.